(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the implementation of reading instruction in early grades by teachers at SDN 6 Sungai Raya. This study uses a qualitative descriptive approach with participants consisting of first, second, and third grade homeroom teachers and the principal. Data were collected through interviews, checklist instruments, and documentation conducted in August 2024. The results of the study indicate that reading instruction in early grades at SDN 6 Sungai Raya has been implemented in accordance with school policies that focus on strengthening basic literacy skills. Instructional activities cover three main aspects, namely planning, implementation, and application of the reading instruction program. These findings indicate that teachers have made efforts to apply reading instruction strategies that are appropriate for the characteristics of early grade students.